Compositional uniqueness of diatoms and insects in subtropical streams is weakly correlated with riffle position and environmental uniqueness - Castro, Emanuela; Siqueira, Tadeu [UNESP]; Melo, Adriano Sanches; Bini, Luis Mauricio; Landeiro, Victor Lemes; Schneck, Fabiana (Springer Nature, 2019)
Some local communities contribute more to beta diversity than others, which has been known as compositional uniqueness or local contribution to beta diversity. Compositional uniqueness should correlate positively with environmental uniqueness and site isolation. We evaluated compositional uniqueness (total and in terms of species replacement and nestedness) of periphytic diatoms and insects in subtropical streams and tested for correlates of these metrics. We sampled 90 riffles in a near-pristine catchment in the southeast Atlantic Forest of Brazil. The total compositional uniqueness for diatoms and insects were not associated to riffle position. However, the total compositional uniqueness of diatoms (presence–absence data), was correlated with the uniqueness of streambed substrate composition, while the total compositional uniqueness of insects did not correlate with any explanatory variable. The compositional uniqueness in terms of nestedness (presence–absence data) for diatoms and for insects (abundance data) was correlated positively with the uniqueness of substrate composition. Compositional uniqueness in terms of species replacement (abundance data) for insects was correlated negatively with the uniqueness of substrate composition. Our results indicate that subtle differences in environmental uniqueness, play a role in determining beta diversity in near-pristine streams. However, finding strong correlates of compositional uniqueness proved to be a difficult task.
Keywords: Compositional variation; LCBD; Nestedness; Replacement